Pengaruh Green Accounting, Kinerja Lingkungan, dan Corporate Social Responsibility terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Ningrum, Safita; Gunarianto, Gunarianto; Hasan, Khojanah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to examine green accounting, environmental performance and corporate social responsibility on profitability in manufacturing companies listed on the IDX in 2019-2021. This research uses a quantitative approach using secondary data with the sample used being 23 companies with a 3 year time period whose data processing was carried out using the IBM application. SPSS 25. The research results show that partially green accounting has a negative effect on company profitability with a sig value of 0.039<0.05. Meanwhile, environmental performance has no influence on profitability because the sig value is 0.133>0.05. And corporate social responsibility has a positive effect on profitability with a sig value of 0.009 <0.05. And the results of research simultaneously green accounting, environmental performance, and corporate social responsibility have a significant influence on company profitability with F test calculation results of 0.012<0.05.